An Adaptive Digital Fuzzy Architecture for Application-Specific Integrated Circuits - N. E. Evmorfopoulos; J. N. Avaritsiotis (Active and Passive Electronic Components)
A generic fuzzy logic system implementation in digital hardware is presented in this paper. The architecture developed is oriented to Application-Specific Integrated Circuits (ASICs), and its functionality is demonstrated through a typical ASIC for a simple control application. Furthermore, a distributed adaptation scheme is proposed for real-time environments. Performance/area tradeoffs for VLSI implementation are also discussed.